Rekonstruksi Perlindungan Hukum bagi Dokter dalam Praktik Telemedicine: Perspektif Undang-Undang Nomor 17 Tahun 2023 tentang Kesehatan - Hadi Wijaya; Charles DL Pardede; Hotman Sinambela (Jurnal Hukum Lex Generalis, 2025)
The development of information technology has brought significant changes in the health sector, one of which is the practice of telemedicine that enables medical services to be provided without spatial and temporal limitations. However, the presence of telemedicine raises new issues related to legal protection for doctors as professionals who perform their duties in accordance with ethical and legal standards. This article aims to analyze the forms of legal protection for doctors in the practice of telemedicine under Law Number 17 of 2023 concerning Health and to identify the challenges encountered in its implementation. This study employs a normative juridical method with statutory and conceptual approaches, supported by the analysis of justice theory, legal certainty, and legal protection. The findings indicate that there are six main forms of legal protection: protection of professional rights and obligations, legal certainty in service standards, liability mechanisms, guarantees of patient data confidentiality, administrative protection through licensing, and ethical protection through professional organization supervision. Nevertheless, its implementation faces several obstacles, such as limited detailed technical regulations, disharmony of norms across legislations, weak digital infrastructure, low legal and technological literacy among medical professionals and patients, and challenges in law enforcement. In conclusion, legal protection for doctors in telemedicine already has a sufficiently strong normative basis, yet remains suboptimal in practice. Therefore, regulatory reconstruction, strengthening the role of professional organizations, and improving human resources and infrastructure are required to establish telemedicine that is accountable, safe, and fair for all parties.